International relations and the challenge of postmodernism defending the discipline - Jarvis, D. S. L. (Darryl S. L.), 1963- (Studies in international relations (Columbia, S.C.), 2000)
By developing a series of critical typologies to assess postmodern and poststructural theories, Jarvis mount a ringing defense of the discipline's exisiting research methods and epistemologies, and he suggests that more harm than good has come of the epistemological subversion occasioned by the Third Debate.